2022
DOI: 10.1039/d2mh00361a
|View full text |Cite
|
Sign up to set email alerts
|

An interfacial floating tumbler with a penetrable structure and Janus wettability inspired by Pistia stratiotes

Abstract: Designing advanced interfacial materials is decisive to the improvement of multiphase systems. Inspired by the superior floatability of Pistia stratiotes, here we present a superhydrophobic/hydrophilic 3D Janus floater possessing a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…A hydrophilic/hydrophobic (HLB) cooperative effect has been considered as a promising strategy to innovate the fluid-manipulating interface toward real-world applications such as catalysis, , vapor condensation, , fog harvesting, , and interfacial floaters. , Typical designs of the hydrophilic/hydrophobic cooperative interface have been proposed before, including the penetrable Janus interface, wettability-patterned surface, and hierarchical structure with selective wettability. In 2015, we reported that the penetrable Janus interface composed of hydrophobic copper mesh and hydrophobic absorbent could achieve an all-in-one fog harvesting process of microdroplet capture, directional transport, and rapid storage .…”
Section: Introductionmentioning
confidence: 99%
“…A hydrophilic/hydrophobic (HLB) cooperative effect has been considered as a promising strategy to innovate the fluid-manipulating interface toward real-world applications such as catalysis, , vapor condensation, , fog harvesting, , and interfacial floaters. , Typical designs of the hydrophilic/hydrophobic cooperative interface have been proposed before, including the penetrable Janus interface, wettability-patterned surface, and hierarchical structure with selective wettability. In 2015, we reported that the penetrable Janus interface composed of hydrophobic copper mesh and hydrophobic absorbent could achieve an all-in-one fog harvesting process of microdroplet capture, directional transport, and rapid storage .…”
Section: Introductionmentioning
confidence: 99%
“…Beneting from its natural design, Pistia could exist peacefully in the aquatic environment for a long time. [51][52][53] A bionic monolithic photocatalyst with a hydrophilic/hydrophobic Janus oatable structure may be prepared by drawing inspiration from Pistia's exceptional physiological function. When the photocatalyst oats on the air-water surface, the plentiful gas reactants may diffuse directly from the air phase to the reaction interface through the hydrophobic part, eliminating the impediment of low solubility and slow diffusion of gaseous reactants in the liquid phase over long distances, and the hydrophilic part guarantees water supply, which can construct a gas-solid-liquid triphase interface, successfully.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 At the same time, Janus materials with super-hydrophobic and super-hydrophilic properties can provide buoyancy and improve adhesion to water at the same time. 40,43 However, Janus materials face the following three hurdles: (1) low load carrying capacity; (2) low adhesion; and (3) poor stability underwater.…”
Section: Introductionmentioning
confidence: 99%